Pemberian Estrak Daun Torbangun pada Ibu Nifas Terhadap Pengeluaran ASI dan Kenaikan Berat Badan Bayi - Febriyanti, Hellen; Sanjaya, Riona; Poniah, Poniah (Journal of Research in Social Science and Humanities, 2021)
If a baby is not given exclusive breastfeeding, it has a bad impact on the baby. The highest coverage for infants aged 0–6 months who received exclusive breastfeeding according to the district / city level in the province of Lampung in 2018 was Pringsewu Regency, namely 78.91%, while for Bandar Lampung City it reached 69.53%. The purpose of this study was to determine the effect of Torbangun leaf extract on breast milk production in post-partum mothers in the State Batin Community Health Center, Kota Agung Barat District, Tanggamus Regency in 2021. This research is a quantitative study with a Quasi-experimental research design. The object of the research was the post-partum mother in the Inner State Health Center. The data was collected using an observation sheet. The subject of this research is the production of breast milk for post-partum mothers. This research was conducted in February 2021 in the State Batin Health Center, Kota Agung Barat District, Tanggamus Regency. The results showed that the average breastmilk production in postpartum mothers before being given Torbangun Leaf Extract in the State Batin Community Health Center, Kota Agung Barat District, Tanggamus Regency in 2020 was 2.133 and after was 55.800. It is known that the average milk production in postpartum mothers after being given Torbangun leaf extract in the State Batin Health Center, Kota Agung Barat District, Tanggamus Regency in 2021 is 2.067 and after is 41.933. There is an effect of Torbangun leaf extract on breast milk production in post-partum mothers in the area of Negara Batin Health Center, Kota Agung Barat District, Tanggamus Regency in 2020 (p-value 0,000). There in’t an effect of Torbangun leaf extract on breast milk production in post-partum mothers in the area of Negara Batin Health Center, Kota Agung Barat District, Tanggamus Regency in 2020 (p-value 0,647). Suggestions Can provide input information to the public about the effect of giving the leaves extract of wakes (coleus ambonicus lour) on postpartum maternal breastfeeding.